Modelling Kepler red giants in eclipsing binaries: calibrating the mixing-length parameter with asteroseismology. Issue 1 (8th December 2017) - Li, Tanda; Bedding, Timothy R; Huber, Daniel; Ball, Warrick H; Stello, Dennis; Murphy, Simon J; Bland-Hawthorn, Joss
Abstract: Stellar models rely on a number of free parameters. High-quality observations of eclipsing binary stars observed by Kepler offer a great opportunity to calibrate model parameters for evolved stars. Our study focuses on six Kepler red giants with the goal of calibrating the mixing-length parameter of convection as well as the asteroseismic surface term in models. We introduce a new method to improve the identification of oscillation modes that exploits theoretical frequencies to guide the mode identification ('peak-bagging') stage of the data analysis. Our results indicate that the convective mixing-length parameter (α) is ≈14 per cent larger for red giants than for the Sun, in agreement with recent results from modelling the APOGEE stars. We found that the asteroseismic surface term (i.e. the frequency offset between the observed and predicted modes) correlates with stellar parameters ( T eff, log g ) and the mixing-length parameter. This frequency offset generally decreases as giants evolve. The two coefficients a −1 and a 3 for the inverse and cubic terms that have been used to describe the surface term correction are found to correlate linearly. The effect of the surface term is also seen in the p–g mixed modes; however, established methods for correcting the effect are not able to properly correct the g-dominated modes in late evolved stars.